(untitled) (El-Wahat Journal for Research and Studies, 2025)
This Research Highlights The Relationship Between Arabic Dialects And Linguistic Standardization By Examining The Grammarians’ Approach To Identifying The Syntactic Particularities Of Arabic Dialects, Their Methods Of Addressing Them, And The Criteria For Their Acceptance Or Reservation. Additionally, It Presents Various Linguistic Issues And Examples While Specifying The Dialect Associated With Each Grammatical Case. Keywords: Arabic Dialects, Linguistic Codification, Arabic Language, Heritage, Grammar,Structual Characteristics.